Effect of National Accreditation Board for Hospital-Recommended Trainings on Patient Care Standards: A Comparative Study Based on the National Quality Assurance Standards Guidelines in a Tertiary Health-care Institute - Vikram Singh; Arvind Kumar Singh; Manish Raj Kulshrestha; Dimpi Singh; Adeeba Khan; Mridu Singh (Indian Journal of Public Health)
Background: The National Quality Assurance Standards (NQAS) have been developed keeping in specific requirements for public health facilities as well global best practices. Standards are primarily meant for providers to assess their quality for improvement through predefined standards and to bring up their facilities for certification. Objectives: To study the effect of National Accreditation Board for Hospitals (NABH)-recommended training on patient care standards based on NQAS guidelines. Materials and Methods: The research was conducted at a tertiary-level teaching institute and medical care center in North India. The institute has multiple blocks, few have undergone training for NABH standards, and few have not due to administrative reasons. Only the NABH-trained blocks underwent accreditation process through NABH and provided an opportunity to study whether there is a difference in patient care standards between NABH-trained staff and nontrained staff. It was a checklist-based observational study. Results: The evaluation covered seven key areas in intensive care unit (ICU) and wards in both NABH-trained and nontrained hospital blocks: patient rights, inputs, support services, clinical services, infection control, quality management, and outcome. The compliance percentage of ICU and wards was measured for NABH-trained and nontrained hospital blocks. NABH-trained blocks in both areas showed better compliance adhering to standards as compared to nontrained blocks for all seven key areas. Conclusion: The study findings indicate that NABH-recommended training showed positive impact on patient care standards as per the NQAS guidelines. The NABH-trained hospital block exhibited superior compliance with various domains including patient rights, inputs, support services, clinical services, infection control, and quality management.